1991
DOI: 10.1159/000204880
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Radiation Therapy in the Management of Hematopoietic Neurologic Complications in Thalassemia

Abstract: Extramedullary hematopoiesis is encountered in some severe anemic conditions. Very rarely it may cause neurologic symptoms, leading to spinal cord or cauda equina compression. Two patients with thalassemia who developed neurologic complications are described. Diagnosis was based on clinical findings, CT scan and magnetic-resonance imaging (MRI). The two patients responded successfully to irradiation and blood transfusion. The prognosis is excellent, if recognized at an early stage. Our experience supports the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
47
0
6

Year Published

1992
1992
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(53 citation statements)
references
References 10 publications
0
47
0
6
Order By: Relevance
“…But as in our case, the reduction of hematopoietic pseudotumors happens slowly and incomplete [6,12]. In patients who need rapid therapeutic response due to severe neurological symptoms, radiotherapy might be considered the primary treatment.…”
Section: Discussionmentioning
confidence: 51%
“…But as in our case, the reduction of hematopoietic pseudotumors happens slowly and incomplete [6,12]. In patients who need rapid therapeutic response due to severe neurological symptoms, radiotherapy might be considered the primary treatment.…”
Section: Discussionmentioning
confidence: 51%
“…6 HU has been associated with increase of the total percentage of fetal hemoglobin and the number of F-cells, as well as the total hemoglobin concentration and mean corpuscular volume in sickle cell patients. 7 Although there is limited experience with HU in thalassemia, some studies have demonstrated successful regression of EMH with HU therapy.…”
Section: Discussionmentioning
confidence: 99%
“…The benefits include ready availability, effectiveness in the resolution of symptoms in a short period of time and reduction of local recurrence. 17 Abassioun and Amir-Jamshidi 8 in 1982 reported the case of a 15-year-old female who was paraparetic with long tract signs. The patient's symptoms resolved after 1500 cGy of radiation in five treatments with only residual right sustained clonus.…”
Section: Discussionmentioning
confidence: 99%